2013
DOI: 10.5173/ceju.2013.04.art3
|View full text |Cite
|
Sign up to set email alerts
|

MMP7 and MMP8 genetic polymorphisms in bladder cancer patients

Abstract: IntroductionBreakdown of the extracellular matrix by matrix metalloproteinases (MMPs), as we know, is one of mechanisms involved and required in tumor invasion. MMP7 is a negative prognostic factor of various malignances, while MMP8 exhibits an inhibitory effect on tumorigenesis and metastasis. We evaluated the potential association of functional polymorphisms in the promoter of the MMP7 (rs11568818) and MMP8 (rs11225395) genes and bladder cancer (BCa) risk.Materials and methodsThe study included 241 BCa cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…also reported an association between genetic polymorphisms in the MMP2 ( rs2285053 ), MMP7 ( rs11568818 ) and MMP8 genes ( rs11225395 ), and no association of genetic polymorphism in the MMP3 gene ( rs520540 ) with BC risk . Our study confirmed no association of genetic polymorphisms in the MMP2 ( rs243865 ), MMP7 ( rs11568818 ), MMP8 ( rs11225395 ), MMP9 ( rs3918242 ) and MMP12 genes ( rs2276109 ) with BC risk in Caucasian population …”
Section: Genetic Polymorphisms In the Mmp Genes As A Modifier Of Bc Rsupporting
confidence: 72%
See 1 more Smart Citation
“…also reported an association between genetic polymorphisms in the MMP2 ( rs2285053 ), MMP7 ( rs11568818 ) and MMP8 genes ( rs11225395 ), and no association of genetic polymorphism in the MMP3 gene ( rs520540 ) with BC risk . Our study confirmed no association of genetic polymorphisms in the MMP2 ( rs243865 ), MMP7 ( rs11568818 ), MMP8 ( rs11225395 ), MMP9 ( rs3918242 ) and MMP12 genes ( rs2276109 ) with BC risk in Caucasian population …”
Section: Genetic Polymorphisms In the Mmp Genes As A Modifier Of Bc Rsupporting
confidence: 72%
“…and Wieczorek et al . showed that MMP1 ( rs1799750 ) is significantly associated with BC risk, namely the 2G2G genotype with OR 2.79 (95% CI 1.53–5.60), 2 G2G genotype with OR 3.04 (95% CI 1.71–5.39) and 2G1G + 1G1G genotype with OR 0.62 (95% CI 0.39–0.98), respectively …”
Section: Genetic Polymorphisms In the Mmp Genes As A Modifier Of Bc Rmentioning
confidence: 99%
“…17Y19 It has been demonstrated that polymorphisms of some MMPs were strongly associated with a risk of cancer, such as prostate cancer, 20 breast cancer, 21,22 lung cancer, 23,24 and bladder cancer. 25,26 It has been reported that the matrix metalloproteinase-1 (MMP1) promoter j1607Ybase pair (bp) polymorphism was a negative prognostic parameter in patients with ovarian cancer. 27 The association between the MMP1 promoter j1607-bp polymorphism and ovarian cancer has been extensively investigated.…”
mentioning
confidence: 99%
“…We also found only one Chinese article in the WanFang database. As a result, 12 case-control articles were included in our meta-analysis: (Hirata et al, 2004;Zhong et al, 2005;Kader et al, 2006;Albayrak et al, 2007;Piccoli et al, 2007;Tasci et al, 2008;Tsuchiya et al, 2009;Srivastava et al, 2010aSrivastava et al, , 2010bWieczorek et al, 2013Wieczorek et al, , 2014Srivastava et al, 2013a) (Fig. 1).…”
Section: Eligible Studiesmentioning
confidence: 99%
“…A quantitative synthesis to accumulate data from different studies is needed to provide better evidence on these associations. Here, in this report, we performed a meta-analysis of 12 publications to estimate the effect of eight polymorphisms: MMP1 -1607 1G/2G (Hirata et al, 2004;Kader et al, 2006;Albayrak et al, 2007;Piccoli et al, 2007;Tasci et al, 2008;Tsuchiya et al, 2009;Srivastava et al, 2010a;Wieczorek et al, 2013), MMP2 -1306 C/T (Zhong et al, 2005;Kader et al, 2006;Srivastava et al, 2013a;Wieczorek et al, 2013), MMP3 (45E/K) G/A (Kader et al, 2006;Srivastava et al, 2010b), MMP7 -181 A/G (Srivastava et al, 2010a;Wieczorek et al, 2014), MMP9 -1562 C/T (Zhong et al, 2005;Kader et al, 2006;Wieczorek et al, 2013), MMP9 (279R/Q) A/G (Kader et al, 2006;Tasci et al, 2008;Srivastava et al, 2010b), and MMP9 (574R/P) T/C (Kader et al, 2006;Srivastava et al, 2010b), MMP9 (668Q/R) A/G (Kader et al, 2006;Srivastava et al, 2010b) on urinary cancer risk.…”
Section: Introductionmentioning
confidence: 99%